1989
DOI: 10.1111/j.1365-2125.1989.tb03561.x
|View full text |Cite
|
Sign up to set email alerts
|

Frusemide, ACE inhibition, renal dopamine and prostaglandins: acute interactions in normal man.

Abstract: 1 The acute effects of intravenous frusemide (30 mg) on prostaglandin dependent renal haemodynamics, urinary prostaglandin excretion, urinary dopamine excretion and electrolyte excretion were studied in six salt replete healthy volunteers with and without pretreatment with the angiotensin converting enzyme (ACE) inhibitor, ramipril (5 mg) and compared with the effects of ramipril alone in order to clarify the role of the reninangiotensin system in these responses.2 Frusemide increased natriuresis (UNaV), kaliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The subjects were apparently not in sodium equilibrium since prior to furosemide administration sodium excretion was approximately 0.15 mmol/min, corresponding to approximately 200 mmol/day on daily salt intake below 60 mmol/day. Our observations are in agreement with those of MacDonald et al [7] who observed increased natriuresis after furosemide in subjects treated with ramipril.…”
Section: Discussionsupporting
confidence: 83%
“…The subjects were apparently not in sodium equilibrium since prior to furosemide administration sodium excretion was approximately 0.15 mmol/min, corresponding to approximately 200 mmol/day on daily salt intake below 60 mmol/day. Our observations are in agreement with those of MacDonald et al [7] who observed increased natriuresis after furosemide in subjects treated with ramipril.…”
Section: Discussionsupporting
confidence: 83%
“…Because the renal tubules are the main source of renal dopamine, renal parenchymal diseases, namely chronic renal failure, are associated with decreased urinary excretion of dopamine [24][25][26]. On the other hand, some medications, namely angiotensin-converting enzyme inhibitors and frusemide, are also known to influence renal dopamine production [27,28]. There is also some evidence that age correlates negatively with plasma levels of L-DOPA and urinary dopamine [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments provide new information that furosemide modulates RBF in an age‐dependent manner. Renal blood flow is enhanced by furosemide in adult animals and humans; 20,21 this forms the basis of its use in the management of acute tubular necrosis and other diseases of renal origin. Previous experiments in adult animals and humans have provided evidence that this renal haemodynamic response to furosemide results from an increase in prostaglandins of the E series 22 .…”
Section: Discussionmentioning
confidence: 99%